Moderenisasi Alat Produksi dan Branding Usaha Keripik Pisang Bagi Ibu Rumah Tangga Keluarga Petani Pisang di Koya Tengah - Theresia Wuri Oktaviani; Endang Hartiningsih; Tiper Korneles Muwarberto Uniplaita (Fakultas Teknik Universitas Cenderawasih, 2025)
The implementation of this community service program aims to modernize the production equipment used by a housewife business group and enhance the branding of their enterprise. This initiative is carried out to improve production efficiency, enhance the neatness of product packaging, and meet the requirements for entry into major retail stores. This effort includes procuring new production equipment, such as digital scales and an electric sealer, as well as applying for a P-IRT (Household Industry Food Production) permit. The results indicate that product weights are now standardized across all packaging, and the packaging appearance has improved significantly. Additionally, production time has increased, as multiple people can now participate in the packaging process using the electric sealer, unlike the previous situation where only one person could operate the packaging process.